Improved Fuzzy Decision System for Energy Bill Reduction in the Context of the Brazilian White Tariff Scenario - Branco, Raimunda; Saraiva, Filipe (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2023: Anais da XII Brazilian Conference on Intelligent Systems, 2023)
The production of energy from renewable sources has become a more sustainable and environmentally correct alternative, where the use of solar energy through photovoltaic systems is evident. One of the main problems in the use of photovoltaic systems is the high cost of installation and maintenance of this system, in addition to the cost of the residential electricity tariff, which makes this technology expensive for most residential consumers in Brazil. An alternative for consumers to get around the high amounts paid on the energy bill is to opt for the white tariff modality, which is characterized by offering the variation of the energy value according to the day and time of consumption. The present work aims to develop a fuzzy system to manage the energy production from a photovoltaic system, optimizing the use of the produced energy between the consumer, the battery and the electric grid in a white tariff scenario for residential units in Brazil. Based on the simulations, the fuzzy system presented is efficient, with a significant economic reduction in the energy bill compared to a simple photovoltaic system without the ability to make intelligent decisions and used commercially in industries.